Neuroprotective Effect of 4-Phenylbutyric Acid against Photo-Stress in the Retina - Guzmán Mendoza, Naymel Alejandra (Antioxidants (Basel), 2021)
Exposure to excessive visible light causes retinal degeneration and may influence the progression of retinal blinding diseases. However, there are currently no applied treatments. Here, we focused on endoplasmic reticulum (ER) stress, which can cause cellular degeneration and apoptosis in response to stress. We analyzed functional, histological, and molecular changes in the light-exposed retina and the effects of administering an ER-stress inhibitor, 4-phenylbutyric acid (4-PBA), in mice. We found that light-induced visual function impairment related to photoreceptor cell loss and outer segment degeneration were substantially suppressed by 4-PBA administration, following attenuated photoreceptor apoptosis. Induction of retinal ER stress soon after light exposure, represented by upregulation of the immunoglobulin heavy chain binding protein (BiP) and C/EBP-Homologous Protein (CHOP), were suppressed by 4-PBA. Concurrently, light-induced oxidative stress markers, Nuclear factor erythroid 2–related factor 2 (Nrf2) and Heme Oxygenase 1 (HO-1), and mitochondrial apoptotic markers, B-cell lymphoma 2 apoptosis regulator (Bcl-2)-associated death promoter (Bad), and Bcl-2-associated X protein (Bax), were suppressed by 4-PBA administration. Increased expression of glial fibrillary acidic protein denoted retinal neuroinflammation, and inflammatory cytokines were induced after light exposure; however, 4-PBA acted as an anti-inflammatory. Suppression of ER stress by 4-PBA may be a new therapeutic approach to suppress the progression of retinal neurodegeneration and protect visual function against photo-stress.